(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
Ternate is an area with active volcanoes, where the center of Ternate City is located on an island with an active volcano, namely Mount Gamalama. This condition indicates that Ternate City is at high risk of the threat of volcanic eruptions. One of the communities that is a priority for disaster management programs is schools. This is because schools can take an active role in improving knowledge and attitudes about disasters, emergency response plans, and their role in disaster mitigation. Therefore, one of the efforts made to increase preparedness in reducing disaster risk is through disaster preparedness training using simulation and video methods. This empowerment aims to provide knowledge to elementary school students regarding preparedness for volcanic eruptions and earthquakes. The activity methods used in this community service are earthquake simulations and videos on disaster preparedness for Mount Erupus. As a result of this activity, 90% of the 60 students experienced increased knowledge and increased experience directly related to being prepared to face volcanic eruptions and earthquakes. It is hoped that schools located at the foot of Mount Gamalama will add material about disaster preparedness to the elementary school curriculum, for example, in scout extracurricular activities. — Ternate adalah salah satu daerah dengan gunung berapi aktif, dimana pusat Kota Ternate terletak di sebuah pulau dimana terdapat gunung berapi aktif, yaitu gunung Gamalama. Kondisi ini mengindikasikan bahwa Kota Ternate menjadi berisiko tinggi terhadap ancaman letusan gunung berapi. Salah satu komunitas yang menjadi prioritas program manajemen bencana adalah sekolah. Hal ini dikarenakan sekolah dapat mengambil peran aktif dalam memperbaiki pengatahuan dan sikap mengenai bencana, rencana tanggap darurat serta peran dalam mitigasi bencana. Oleh karena itu, salah satu upaya yang dilakukan dalam meningkatkan kesiapsiagaan dalam pengurangan risiko bencana adalah melalui pelatihan siaga bencana menggunakan metode simulasi dan video. Tujuan dari pemberdayaan ini adalah untuk memberikan pengetahuan kepada siswa sekolah dasar mengenai kesiapsiagaan menghadapi bencana gunung Meletus dan gempa bumi. Metode kegiatan yang digunakan dalam Pengabdian masyarakat ini adalah simulasi gempa bumi dan video kesiapsiagaan bencana gunung Meletus. Hasil dari kegiatan ini dari 60 siswa, 90% mengalami peningkatan pengetahuan dan bertambahnya pengalaman secara langsung terkait dengan siap siaga menghadapi bencana gunung Meletus dan gempa bumi. Diharapkan sekolah yang berada di bawah kaki gunung Gamalama perlu menambahkan materi tentang disaster preparedness ke dalam kurikulum sekolah dasar,misalnya dalam kegiatan ekstrakurikuler pramuka.